Home Sweet Home. - Karcher, Eva; Zdenek, Felix; Deichtorhallen, Hamburg (Köln : Oktagon, 1997)
Althoff, Kai ; Armleder, John M. ; von Bonin, Cosima ; Billingham, Richard ; Büttner, Werner ; Fleury, Sylvie ; Green, Renée ; Grünfeld, Thomas ; Kelley, Mike ; Kippenberger, Martin ; Lichtenstein, Roy ; Möller, Regina ; Pardo, Jorge ; Peterman, Dan ; Rehberger, Tobias ; Rosenquist, James ; Schulze, Andreas ; Taylor-Wood, Sam ; Vincourova, Katerina ; West, Franz ; Zehrer, Joseph
biog., ind. tent. p.75-86
Duits
Home Sweet Home, Deichtorhallen Hamburg, 20. Juni bis 28. September 1997
boek